Learning through Linguistic citizenship: Finding the “I” of the essay - Bock, Zannie; Abrahams, Lauren; Jansen, Keshia (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In recent years, the South African higher education system has seen growing calls for broadened epistemic access, decolonised curricula and transformed institutions. Scholars across South Africa have taken up the challenge and are working on new theoretical approaches to teaching and learning in higher education. In this paper, we reflect on students’ experiences of a multilingual, multimodal module called Reimagining Multilingualisms, which was jointly offered by the Universities of the Western Cape and Stellenbosch in April and May of 2018. In this paper, we provide an overview of the module and the different types of activities it involved. We reflect on these experiences using the theoretical lenses of decolonial scholar Mignolo (2009) on the ‘locus of enunciation’, and Stroud (2018) on ‘Linguistic Citizenship’. We present extracts from focus group interviews with students from both campuses to illustrate the involvement of ‘the body’ in ‘knowing’ and the ways in which the module enabled different ‘voices’ to emerge. We focus particularly on the role played by students’ perceived ‘vulnerability’ in the transformative benefits of the module and discuss this by way of conclusion. In sum, we suggest how the centring of multilingualism and diversity – not only as core pedagogic principles, but also as a methodology for transformation – may be used to enhance access and recapture voice in the building of a more integrated and just society.